Implementasi Promotion mix Pada PT Batam Roda Jaya - Stanley Frenovsky Leowardi; Edy Yulianto Putra (Cv. Utility Project Solution, 2023)
Batam Roda Jaya is a company in the form of a limited liability company (PT) engaged in the distribution sector. PT Batam Roda Jaya while carrying out its business activities has a problem, namely not having active marketing. For this reason, in helping partners, promotion mix is a strategy used to increase sales. The promotion mix used at PT Batam Roda Jaya is through promotion in terms of advertising and sales promotion. The data collection technique used was observation and interviews with 3 stages, namely the preparation stage, the implementation stage, and the assessment and reporting stage. Promotion mix implemented through social media, namely Instagram and Facebook. Then, register and input products on e-commerce on the Shopee platform and make price discounts on certain days. The author also makes a manual book that makes it easy for employees and partner owners to run the project. The implementation of digital marketing will help partners market their products to a wider market, not only in Batam city but throughout Indonesia.